A new species of Huarpea Pate, 1947 (Hymenoptera, Sapygidae) from the semiarid region of Brazil - Botion Lopes, Rogério; Pereira Moleiro, Henrique; Lucena, Daercio A.A. [UNESP] (My University, 2024)
The genus Huarpea is recorded for the first time in northeastern Brazil. A new species, H. rotundicornis Lopes, Moleiro & Lucena, sp. nov., is described and illustrated. The new species represents the first record of Huarpea in the Brazilian semiarid region, and the easternmost record of this genus in South America. A revised key for all known species of Huarpea, with illustrations of diagnostic features, as well as geographical distribution maps are also presented.
Keywords: Bahia; caatinga vegetation; cleptoparasites; Neotropical region; Pompiloidea; Rio Grande do Norte